2009
DOI: 10.1111/j.1365-2702.2009.02857.x
|View full text |Cite
|
Sign up to set email alerts
|

Instructive messages from Chinese nurses’ stories of caring for SARS patients

Abstract: The preparation of a knowledgeable, cared-for nursing workforce promises optimal outcomes with the emergence of the next global infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
118
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(134 citation statements)
references
References 19 publications
12
118
3
Order By: Relevance
“…Chung et al (2005) identified that nurses were motivated by an atmosphere of "non-hierarchical team spirit" (p. 515) across multiple disciplines in the workplace, which resulted in a greater intention to respond to an epidemic event, as a high degree of collegiality would be generated in such conditions. Respondents in Liu and Liehr's (2009) study also mentioned a similar perspective on peer support regarding …”
Section: Professional Valuementioning
confidence: 78%
See 4 more Smart Citations
“…Chung et al (2005) identified that nurses were motivated by an atmosphere of "non-hierarchical team spirit" (p. 515) across multiple disciplines in the workplace, which resulted in a greater intention to respond to an epidemic event, as a high degree of collegiality would be generated in such conditions. Respondents in Liu and Liehr's (2009) study also mentioned a similar perspective on peer support regarding …”
Section: Professional Valuementioning
confidence: 78%
“…The events focused on were the SARS outbreak (Chung, Wong, Suen, & Chung, 2005;Liu & Liehr, 2009;Shih et al, 2007Shih et al, , 2009, the H1N1 pandemic (Lam & Hung, 2013), nonspecified emerging respiratory infectious disease outbreaks (Koh, Hegney, & Drury, 2012) and nonspecified epidemic events (O'Boyle, Robertson, & Secor-Turner, 2006). Two studies employed a two-step within-method qualitative triangulation design (Shih et al, 2007(Shih et al, , 2009; one study adopted a phenomenological approach ; one study used a descriptive exploratory method (Liu & Liehr, 2009); and three studies adopted a simple qualitative design (Koh et al, 2012;Lam & Hung, 2013;O'Boyle et al, 2006). Two studies employed a two-step within-method qualitative triangulation design (Shih et al, 2007(Shih et al, , 2009; one study adopted a phenomenological approach ; one study used a descriptive exploratory method (Liu & Liehr, 2009); and three studies adopted a simple qualitative design (Koh et al, 2012;Lam & Hung, 2013;O'Boyle et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations